Choroidal Thickness in Chinese Children Aged 8 to 11 Years with Mild and Moderate Myopia - Ya Qi; Li Li; Fengju Zhang (Journal of Ophthalmology)
Purpose. To investigate macular choroidal thickness (CT), topographical variation, and associations between subfoveal choroidal thickness (SFCT) and age, gender, spherical equivalent (SE), and axial length (AL) in Chinese healthy mild and moderate myopia children aged 8 to 11 years. Methods. One hundred twenty eyes from 120 healthy children were studied. Children were divided into mild and moderate myopia groups. AL and CT were evaluated. CTs were measured at the fovea, and 1 mm, 2 mm, and 3 mm nasal, temporal, superior, and inferior to the fovea. Results. SFCT was 252.80 ± 46.95 µm in the whole population. AL was shorter in the mild myopia group (24.18 ± 0.69 mm) than in the moderate myopia group (24.97 ± 0.68 mm, P<0.001), and SFCT was thicker in the mild myopia group (262.00 ± 40.57 µm) than in the moderate myopia group (236.00 ± 55.08 µm, P=0.005). The topographical variation was similar in refraction groups. CTs nasal to the fovea thinned gradually and were all significantly thinner than SFCT. CTs in the other three directions gradually thickened and peaked at locations of 2 mm to the fovea. Then, CTs thinned at 3 mm to the fovea. The thickest choroid is located temporal to the fovea. There were significant negative correlations between AL and SFCT in the mild myopia group and the whole population. No other correlations were found. Conclusions. The topographical variations of choroidal thickness were similar in mild and moderate myopia groups with the thickest locations temporal to the fovea. SFCT was relatively stable in children in narrow range of age and refractive error.